2018
DOI: 10.1186/s13104-018-3678-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of fine needle aspiration biopsy in pediatric small round cell tumors

Abstract: ObjectiveFine needle aspiration biospy (FNAB) is a simple, cost effective procedure, which can be carried out in the out-patient department. The objective of our study was to determine the diagnostic accuracy of fine needle aspiration biopsy in small round cell tumors of childhood, keeping histopathology as the gold standard.ResultsOut of these 50 cases, 35 (70%) were small round cell tumors and 15 (30%) cases of other childhood malignancies and certain reactive conditions. In our study, the most common malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…There are diverse etiologies of enlarged lymph nodes, ranging from benign reactive lymphadenopathy (viral or bacterial infections), including tuberculosis (TB) to metastatic carcinomas and lymphomas. Fine needle aspiration cytology (FNAC) without radiological guidance is a quick, effective and relatively inexpensive technique to evaluate visibly accessible superficial masses [1][2][3]. Although the diagnostic material obtained by FNAC is considered of inferior quality than trucut/core needle biopsy, especially for the diagnosis of lymphomas, however, there are many advantages of FNAC over trucut biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…There are diverse etiologies of enlarged lymph nodes, ranging from benign reactive lymphadenopathy (viral or bacterial infections), including tuberculosis (TB) to metastatic carcinomas and lymphomas. Fine needle aspiration cytology (FNAC) without radiological guidance is a quick, effective and relatively inexpensive technique to evaluate visibly accessible superficial masses [1][2][3]. Although the diagnostic material obtained by FNAC is considered of inferior quality than trucut/core needle biopsy, especially for the diagnosis of lymphomas, however, there are many advantages of FNAC over trucut biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Fine needle biopsy is a simple, safe and reliable technique without contraindications, in the diagnosis of non-Hodgkin lymphoma. It has been demonstrated that the diagnostic accuracy of this procedure was 91.4% in the study of Asim et al 11 It provides material for morphologic analysis and other ancillary studies (immunohistochemistry, genetic analysis). 11 However, when the material is limited, the accurate diagnosis becomes difficult, as it needs exhaustive IHC panel to rule out differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the diagnostic accuracy of this procedure was 91.4% in the study of Asim et al 11 It provides material for morphologic analysis and other ancillary studies (immunohistochemistry, genetic analysis). 11 However, when the material is limited, the accurate diagnosis becomes difficult, as it needs exhaustive IHC panel to rule out differential diagnosis. Thus, pathological material with optimal quantity and quality is mandatory to allow performing all the required tests for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing availability and improving efficacy of chemotherapeutic drugs leading to changing role of pre-operative neoadjuvant chemotherapy, accurate cytologic sub-typing of tumors provides an opportunity to the clinician in achieving effective tumor response. [ 15 ] However, there still would be a fraction of cases that would not be amenable to sub-typing on cytology and this should be kept in mind by both the cytopathologist and the referring clinicians.…”
Section: Discussionmentioning
confidence: 99%